EULAR evidence based recommendations for the management of hand osteoarthritis: Report of a Task Force of the EULAR Standing Committee for International Clinical Studies Including Therapeutics (ESCISIT). (17th October 2006) - Zhang, W; Doherty, M; Leeb, B F; Alekseeva, L; Arden, N K; Bijlsma, J W; Dinçer, F; Dziedzic, K; Häuselmann, H J; Herrero-Beaumont, G; Kaklamanis, P; Lohmander, S; et al.
Abstract : Objectives: To develop evidence based recommendations for the management of hand osteoarthritis (OA). Methods: The multidisciplinary guideline development group comprised 16 rheumatologists, one physiatrist, one orthopaedic surgeon, two allied health professionals, and one evidence based medicine expert, representing 15 different European countries. Each participant contributed up to 10 propositions describing key clinical points for management of hand OA. Final recommendations were agreed using a Delphi consensus approach. A systematic search of Medline, Embase, CINAHL, Science Citation Index, AMED, Cochrane Library, HTA, and NICE reports was used to identify the best available research evidence to support each proposition. Where possible, the effect size and number needed to treat were calculated for efficacy. Relative risk or odds ratio was estimated for safety, and incremental cost effectiveness ratio was used for cost effectiveness. The strength of recommendation was provided according to research evidence, clinical expertise, and perceived patient preference. Results: Eleven key propositions involving 17 treatment modalities were generated through three Delphi rounds. Treatment topics included general considerations (for example, clinical features, risk factors, comorbidities), non-pharmacological (for example, education plus exercise, local heat, and splint), pharmacological (for example, paracetamol, NSAIDs, NSAIDs plus gastroprotective agents, COX-2 inhibitors, systemic slow acting disease modifying drugs, intra-articular corticosteroids), and surgery. Of 17 treatment modalities, only six were supported by research evidence (education plus exercise, NSAIDs, COX-2 inhibitors, topical NSAIDs, topical capsaicin, and chondroitin sulphate). Others were supported either by evidence extrapolated from studies of OA affecting other joint sites or by expert opinion. Strength of recommendation varied according to level of evidence, benefits and harms/costs of the treatment, and clinical expertise. Conclusion: Eleven key recommendations for treatment of hand OA were developed using a combination of research based evidence and expert consensus. The evidence was evaluated and the strength of recommendation was provided.